Työterveyspalveluiden yhteys työntekijöiden koettuun työhyvinvointiin ja sairauspoissaoloihin - Talka, Adam; Mäkelä, Tuukka (2025)
Mäkelä, T. & Talka, A. 2025. The Associations Between Occupational Health Services and Employees’ Perceived Well-Being and Sick Leave. Faculty of Sport and Health Sciences, Uni-versity of Jyväskylä, (Sport and Exercise Medicine) Master’s Thesis, 78 pages, 4 appendices.